Self-compacting concrete use for construction work environment sustainability - Rwamamara, Romuald; Simonsson, Peter (Journal of Civil Engineering and Management, 2018)
Many of those working on construction sites are exposed to demanding work loads; construction workers lift and carry heavy materials and work in awkward postures. Occupational injuries and accidents due to poor ergonomics are more common in the construction industry and many times lead to human tragedies, disrupt construction processes and adversely affect the cost, productivity, and the reputation of the construction industry. In Sweden, it is reported that concrete workers have the highest relative work-related musculoskeletal injury frequency. Therefore, the use of ergonomic production methods to prevent this can have a significant human, social and financial impact. Research introduced here presents a case study of comparative analyses of ergonomic situations for concrete workers performing concrete casting processes. Three different ergonomic risk assessment methods were used to assess the physical strain, hand-arm vibration and noise affects risks involved in concrete casting work tasks. The combination of technical and managerial factors results in a system where workers are as efficient and safe as possible during their work tasks, and thus, makes the construction work environment sustainable. The aim of our research is to find practical methods to evaluate and compare two different concrete casting methods from an ergonomic perspective. The focus is on the production of cast-in-place concrete bridge constructions where the traditional concrete casting method is compared with the SCC (Self-Compacting concrete) casting method. To be able to identify work-related musculoskeletal injury risks due to concrete casting work tasks, QEC (Quick Exposure Check for musculoskeletal risks), PLIBEL (Checklist for identification for Ergonomics Hazards) and ErgoSAM (Ergonomic production technology method) methods were used. Ergonomic risks analysis methods QEC, PLIBEL and ErgoSAM have all shown capabilities to evaluate construction work activities and thus determine whether a construction work activity constitutes a musculoskeletal risk to the worker or not before any ergonomic intervention is introduced. As a result the present ergonomic risks emanating from work methods used in the traditional concrete placing can be significantly reduced with the use of self-compacting concrete (SCC) that eliminates awkward work postures, noise and hand arm vibration, thereby reducing if not eliminating musculoskeletal injuries among concrete workers during their concrete casting work tasks.